Regulator of Chromosome Condensation 1-Domain Protein DEK47 Functions on the Intron Splicing of Mitochondrial Nad2 and Seed Development in Maize - Cao, Shi-Kai; Liu, Rui; Sayyed, Aqib; Sun, Feng; Song, Ruolin; Wang, Xiaomin; Xiu, Zhihui; Li, Xiaojie; Tan, Bao-Cai (Frontiers in Plant Science, 2021)
In flowering plants, mitochondrial genes contain approximately 20-26 introns. Splicing of these introns is essential for mitochondrial gene expression and mitochondrial function. Recent studies have revealed that both nucleus- and mitochondrion-encoded factors are required for intron splicing, but the mechanism of splicing remains elusive. Elucidation of the mechanism necessitates a complete revelation of the splicing factors. Here we report the identification of an RCC1-domain protein DEK47 in mitochondrial intron splicing and seed development in maize. Loss of function in Dek47 severely arrests embryo and endosperm development, leading to a defective kernel (dek) phenotype. DEK47 harboring seven RCC1 domains is targeted to mitochondria. Null mutation of DEK47 causes a deficiency in the splicing of all four nad2 introns, abolishing production of the mature nad2 transcript, and resulting in disassembly and severely reduced activity of mitochondrial complex I. In response, expression of the alternative oxidase AOX2 is sharply increased in dek47. These results indicate that Dek47 is required for the splicing of all the nad2 introns in mitochondria, and is essential for complex I assembly, and kernel development in maize.